2021
DOI: 10.1101/2021.03.25.436952
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pyrethroid and metal residues in different coffee bean preparing processes and their human health risk assessments via consumption

Abstract: The study was conducted on 50 samples of coffee beans from various origins. The samples included green coffee beans, roasted beans, brew coffee drinks and coffee sludge. Three processes were used to prepare these samples: dried, semi-washed, and washed. Three synthetic pyrethroid insecticides and nine heavy metals were subsequently analyzed using modified Quick, Easy, Cheap, Effective, Rugged and Safe (QuEChERS) and acid digestion methods, respectively. The quantification of pyrethroids was performed by GC-µEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The results of Arvay et al ( 2018) [53] on Cr concentration were 0.12 mg/kg in green beans and 0.03 mg/kg in roasted beans, which represent a reduction of around 75%. Khunlert et al (2021) [67] determined that Cr and Pb increased slightly after roasting and had a different extraction percentage with infusion (i.e., 23% of Cr and 1.2% of Pb present in roasted coffee). Adler et al (2019) [45] found that roasting has different effects on Pb concentration: one sample suffered a reduction of 86%, while in another, Pb increased by 64% after roasting.…”
Section: Predictive Modelingmentioning
confidence: 99%
“…The results of Arvay et al ( 2018) [53] on Cr concentration were 0.12 mg/kg in green beans and 0.03 mg/kg in roasted beans, which represent a reduction of around 75%. Khunlert et al (2021) [67] determined that Cr and Pb increased slightly after roasting and had a different extraction percentage with infusion (i.e., 23% of Cr and 1.2% of Pb present in roasted coffee). Adler et al (2019) [45] found that roasting has different effects on Pb concentration: one sample suffered a reduction of 86%, while in another, Pb increased by 64% after roasting.…”
Section: Predictive Modelingmentioning
confidence: 99%